Hubungan Dukungan Sosial Dan Self Esteem Dengan Subjective Well Being Pada Mahasiswa Universitas Islam 45 Bekasi - Dita Rama Dhania Chaeruman; Fahira Izza Nabila; Jeineva Choli; Lucky Purwantini (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
The study aimed to explore the connection between social support, self-esteem, and subjective well-being in psychology students at the Islamic University 45 Bekasi. The research involved ≤ 135 participants aged 18–25, actively enrolled in the psychology program for the class of 2021. Simple random sampling was employed for data collection. The findings revealed a positive correlation (0.551) between social support (X1) and subjective well-being (Y), suggesting a significant contribution of social support to the participants' well-being. Additionally, the correlation coefficient between self-esteem (X2) and subjective well-being (Y) was 0.743, indicating a positive and substantial influence of self-esteem on subjective well-being.